إدارة التغيير وأثرها على أداء العاملين بالمديرية الجهوية للجمارك بالشلف: Change management and its impact on the performance of employees at the Regional Directorate of Customs in Chlef - الحاج نعاس خديجة (Journal of North African Economies, 2025)
This study aims to determine the impact of management change with its dimensions (change in organizational structure, change in the management of individuals and change in technology) on the performance of customs directorate workers, its importance in improving the public service, upgrading the customs public facility, and through the analytical study of the distributed questionnaire to a sample of (185) employees at the level of The Regional Directorate of Customs in Chlef, we arrived to a set of results, the most important one was the existence of a statistically significant impact on the change of management in with its dimensions (change in organizational structure, change in technology, change in the management of individuals) on the performance of employees of the Regional Directorate of Customs in Chlef from the point of view of the sample of the study, also that the dimensions of the change of management in this study explained 0.570 of the variable variation (workers performance), this has a positive impact on the development of performance despite of the various obstacles to achieving this endeavour. The study presents a number of recommendations, the most important of which is to provide legal, social, political and economic requirements that would enhance the success of the process of change.